Subcutaneous implantable cardioverter-defibrillator lead repositioning due to device sensing impairment in a patient with scoliosis - Mahsa Nourani; Mahdiyeh Mahdinejadshani; Samira Shirazi; Seyed Ali Pourmomeni; Farzad Kamali (Research in Cardiovascular Medicine, 2023)
Despite many well-documented benefits of the transvenous implantable cardioverter-defibrillator in appropriate patients, there is a strong preference today for subcutaneous implantable cardioverter-defibrillator (S-ICD) implantation due to the significant late complications associated with intravenous leads, especially in young patients. We report on an 18-year-old woman with S-ICD due to hypertrophic cardiomyopathy who had idiopathic dextroscoliosis. In the follow-up analysis, we observed a disturbance in the normal detection of QRS complexes by the device, which significantly reduced when the patient changed the position from standing to supine and when the brace was closed. According to the absence of lead displacement in the chest radiograph, S-ICD sense impairment was suggested due to skeletal deformity. Due to not solving this problem with device reprogramming, we had to reposition of the S-ICD lead in our patient.